2019
DOI: 10.1108/bij-08-2018-0264
|View full text |Cite
|
Sign up to set email alerts
|

Forewarned is forearmed

Abstract: Purpose Internet of Things (IoT) interconnects many heterogeneous devices to each other, collecting and processing large volumes of data for decision making without human intervention. However, the information security concern it brings has attracted quite a lot of attention, and, at this stage, the smart step would be to analyze the security issues of IoT platform and get to the state of readiness before embarking upon this attractive technology. The purpose of this paper is to address these issues. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 137 publications
(190 reference statements)
0
9
0
Order By: Relevance
“…Juliadotter and Choo [119] 2015 Risk Theoretical Both Otero [120] 2015 Risk Theoretical Defender Solic et al [121] 2015 Risk Theoretical Defender Sugiura et al [122] 2015 Risk Theoretical Defender Wei et al [123] 2015 Risk Theoretical Defender You et al [75] 2015 Security Theoretical Defender Brožová et al [51] 2016 Risk Theoretical Defender Brynielsson et al [124] 2016 Awareness Theoretical Defender Granåsen and Andersson [125] 2016 Resilience Theoretical Defender Orojloo and Azgomi [126] 2016 Risk Theoretical Attacker Aiba and Hiromatsu [127] 2017 Risk Theoretical Defender Damenu and Beaumont [103] 2017 Risk Implementation Defender Ramos et al [41] 2017 Review -Defender Rass et al [52] 2017 Risk Theoretical Defender Alohali et al [128] 2018 Risk Theoretical Defender Li et al [82] 2018 Risk Theoretical Defender Morrison et al [43] 2018 Review -Both Pramod and Bharathi [129] 2018 Risk Theoretical Defender Proença and Borbinha [89] 2018 Maturity Implementation Defender Rueda and Avila [130] 2018 Risk Theoretical Defender Shokouhyar et al [104] 2018 Risk Theoretical Defender Stergiopoulos et al [131] 2018 Risk Theoretical Defender You et al [132] 2018 Maturity Theoretical Defender Akinsanya et al [133] 2019 Maturity Theoretical Defender Bharathi [134] 2019 Risk Theoretical Defender Fertig et al [135] 2019 Awareness Theoretical Defender Husák et al [31] 2019 Review -Defender Salih et al [136] 2019 Risk Theoretical Defender Cadena et al [34] 2020 Review -Defender Wirtz and Heisel [137] 2020 Risk Theoretical Defender Ganin et al [138] 2020 Risk Theoretical Defender Luh et al [90] 2020 Risk Theoretical Both Table A3. The in...…”
Section: Validation Methodsmentioning
confidence: 99%
“…Juliadotter and Choo [119] 2015 Risk Theoretical Both Otero [120] 2015 Risk Theoretical Defender Solic et al [121] 2015 Risk Theoretical Defender Sugiura et al [122] 2015 Risk Theoretical Defender Wei et al [123] 2015 Risk Theoretical Defender You et al [75] 2015 Security Theoretical Defender Brožová et al [51] 2016 Risk Theoretical Defender Brynielsson et al [124] 2016 Awareness Theoretical Defender Granåsen and Andersson [125] 2016 Resilience Theoretical Defender Orojloo and Azgomi [126] 2016 Risk Theoretical Attacker Aiba and Hiromatsu [127] 2017 Risk Theoretical Defender Damenu and Beaumont [103] 2017 Risk Implementation Defender Ramos et al [41] 2017 Review -Defender Rass et al [52] 2017 Risk Theoretical Defender Alohali et al [128] 2018 Risk Theoretical Defender Li et al [82] 2018 Risk Theoretical Defender Morrison et al [43] 2018 Review -Both Pramod and Bharathi [129] 2018 Risk Theoretical Defender Proença and Borbinha [89] 2018 Maturity Implementation Defender Rueda and Avila [130] 2018 Risk Theoretical Defender Shokouhyar et al [104] 2018 Risk Theoretical Defender Stergiopoulos et al [131] 2018 Risk Theoretical Defender You et al [132] 2018 Maturity Theoretical Defender Akinsanya et al [133] 2019 Maturity Theoretical Defender Bharathi [134] 2019 Risk Theoretical Defender Fertig et al [135] 2019 Awareness Theoretical Defender Husák et al [31] 2019 Review -Defender Salih et al [136] 2019 Risk Theoretical Defender Cadena et al [34] 2020 Review -Defender Wirtz and Heisel [137] 2020 Risk Theoretical Defender Ganin et al [138] 2020 Risk Theoretical Defender Luh et al [90] 2020 Risk Theoretical Both Table A3. The in...…”
Section: Validation Methodsmentioning
confidence: 99%
“…Irrespective of this relatively low ranking, it is not in doubt that human capital, as well as the organisational climate and culture, play a crucial role in the success of technological solutions according to Zdravkovi c et al (2018). What is also not in doubt, based on the findings from the interviews, is that many organisations are reluctant to invest in IoT until technological issues such as standardisation, IoT information security risks (Bharathi, 2019), wide area networks, integration and compatibility are resolved. For example, it has been highlighted that technology integration is one of the major challenges hindering IoT implementation (Haddud et al, 2017;Ahamed et al, 2021).…”
Section: The Role Of Enabling Factors In Achieving Different Outcomesmentioning
confidence: 99%
“…Shin and Park (2017) identified the importance of the cultural fit of IoT to the users while Tu (2018) also found that key organisational issues such as cost of implementation could act as barriers to IoT adoption. Among a range of technical issues that the industry is facing, key issues include cyber-attacks due to interoperability with multidevices (Rejikumar et al, 2019) and information security risks (Bharathi, 2019). According to Soltani (2022), understanding of relationship management within the context of IoT remains limited and for these reasons, it is important that organisations reach a state of readiness before commencing with IoT (Bharathi, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Internet of Things (IoT) technology has simplified our daily routine by interconnecting smart devices, applications, and services that significantly influence our decision-making processes and lifestyles (Bharathi, 2019). In addition, it influences economic activity across different industries and affects their strategic decisions, investment, and productivity (Goyena and Fallis, 2019).…”
Section: Introductionmentioning
confidence: 99%